Feasibility of preemptive pharmacogenetic testing and improvement of medication treatment satisfaction among medically underserved patients - Christelle Lteif; Elizabeth Eddy; Joshua Terrell; Larisa H. Cavallari; John Malaty; Julio D. Duarte (Wiley, 2024)
Abstract Previous findings suggest that medically underserved patients are prescribed medications with pharmacogenetic (PGx) guidelines at a high frequency. Thus, underserved patients may especially benefit from PGx testing, but little evidence exists regarding the effect of testing in this population. This pilot study aimed to generate key feasibility data and explore clinical outcomes of PGx implementation in underserved populations. Black and Latino patients were recruited from an outpatient clinic and underwent PGx testing. Feasibility measures included enrollment metrics and actionable genotype frequencies. The primary clinical outcome was patient medication treatment satisfaction 6 months after testing. Implementation outcomes included the number of healthcare provider encounters and medication changes within the 6‐month follow‐up. Effectiveness outcomes included medication adherence, patient‐perceived test value, and time spent discussing medications with providers. Ninety‐nine patients completed the study. Proton‐pump inhibitors were the most frequent PGx drug class prescribed at baseline (61%) followed by nonsteroidal anti‐inflammatory drugs (36%). Patients with an actionable genotype constituted 96% of the population, whereas 28% had an actionable genotype related to their PGx drug. Patient treatment satisfaction significantly increased over the 6 months after PGx testing. In addition, medication adherence and the number of provider encounters significantly increased over the study period. In a pilot study, preemptive PGx testing was feasible in primary care clinics, improved patient treatment satisfaction and adherence, and increased the number of provider encounters in medically underserved patients. Future clinical trials are warranted to assess the long‐term effects of PGx testing in a larger diverse patient population.